SISTEM INFORMASI E-LEARNING Di SEKOLAH - Hardinal Fahmi Syaputra (LPPM Nusa Mandiri, 2017)
The learning process is generally carried out directly, but now can be done without a process-face in directly between teachers and students, because now online learning has become a trend at schools, now a national exam using the online system. Development of an e-learning information system created using the waterfall method is to analyze the needs of the system, creation of information systems, to testing. after going through the circuit produced an e-learning information system that can facilitate the learning process between teachers and students online